Paradigm shifts in neonatal hypoxic-ischemic encephalopathy therapeutics: a four-decade bibliometric exploration of emerging therapeutic dimensions (1985–2024) - Shu, Juntao; Liu, Ling; Yuan, Mei; Ma, Mingbiao; Yang, Jingjing (Frontiers in Pediatrics, 2025)
AimNeonatal hypoxic-ischemic encephalopathy (HIE) remains a significant cause of neonatal morbidity and mortality worldwide, necessitating the exploration of effective therapeutic interventions. Current treatment strategies primarily involve therapeutic hypothermia (TH); however, its efficacy remains inconsistent. Research topics and trends in this area remain unclear as well. This study aimed to identify key research areas, collaboration networks, and emerging trends using bibliometric analysis tools.MethodsA comprehensive analysis was conducted on 1,165 records from the Web of Science Core Collection (WoSCC) database. Various bibliometric techniques were employed, including coauthor analysis, co-occurrence analysis, co-citation analysis, reference clustering, and topic modeling, to visualize the knowledge structure and research dynamics in the HIE field.ResultsThe findings revealed extensive collaboration networks among authors, institutions, and countries, highlighting global efforts to address this critical neonatal condition. Recent trends identified key research areas, including TH, mild systemic hypothermia, oxidative stress, biomarkers and signaling pathways, which are essential for advancing the understanding and treatment of HIE.ConclusionThis study provides valuable insights into the current TH for neonates with HIE. Future research should focus on optimizing treatment approaches and evaluating long-term efficacy to enhance clinical applications.